Species composition, distribution and abundance of trees on a 4-hectare site adjacent to the football field area of UPV Miagao,, Iloilo. - Alpuerto, Alise Raymond
A four-hectare plot adjacent to the Football Field of UPV Miagao was chosen as the study area. The local name and scientific name of each tree in the plot were identified. GBH and height of trees were noted. Basal Area, Index of Dominance, Index of diversity and Frequency were also noted. In addition, the distribution of trees in relation with soil and air temperature and relative humidity were also noted., Eight hundred fifty-eight trees were identified inside the 4 hectare plot. The trees were identified excluding seedlins of these trees. Twenty species of trees were identified in the sampling site. The top 5 most numerous species are Acacia, "Aratilis", "Mangga", "Kawayan", and Gmelina". The computed value of Index of Dominance is higher compared to the Index of Diversity, indicating that the area is not diverse and that certain species dominates the area. The distribution of trees is affected by the temperature ranging from 19.2 C to 39C.